DESIGN OF SCIENCE MOBILE LEARNING OF ECLIPSE PHENOMENA WITH CONSERVATION INSIGHT ANDROID-BASED APP INVENTOR 2 (Jurnal Pendidikan IPA Indonesia, 2016)
Learning application is a medium that can be used to convey the content of the material involving mobile devices such as mobile phones based on Android. Learning Phenomens of Eclipse is android-based multimedia application that is created as a supplementof science instructional material in concepts of eclipses that can be accessed using a mobile device such as mobile phone. The methodology used to make this application is waterfall methodology. The purpose of making the application is the conception of conservation and science mobile learning is expected to help the students in particular and scientific community in general to get the ease of learning the concept of solar and lunar eclipses using a smartphone device without having to print using paper (paperless). The application also comes with interactive features of images, videos and quizzes. The conclusion is that mobile learning science applications of eclipse phenomenon  in conception of conservation is developed and feasible to be used to study the concept of  eclipse and support theefforts to reduce the use of paper (paperless).